2010
DOI: 10.1016/j.crhy.2009.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Radio wave propagation in arch-shaped tunnels: Measurements and simulations by asymptotic methods

Abstract: International audienceSeveral wireless communication systems are developed for communication needs between train and ground and between trains in the railway or mass transit domains. They are developed for operational needs for security and comfort. In order to deploy these systems in specific environments, such as tunnels, straight or curved, rectangular or arch-shaped section, specific propagation models have to be developed. A modelisation of the radio wave propagation in straight arch-shaped tunnels is rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Because wave propagation is possible only above a specific cutoff frequency that is determined by the tunnel dimensions and cross-sectional shape, many studies have focused on the shape of the tunnel to analyse the electromagnetic field distribution therein [3]. There are few reports on electromagnetic wave measurements in real underground mine galleries.…”
mentioning
confidence: 99%
“…Because wave propagation is possible only above a specific cutoff frequency that is determined by the tunnel dimensions and cross-sectional shape, many studies have focused on the shape of the tunnel to analyse the electromagnetic field distribution therein [3]. There are few reports on electromagnetic wave measurements in real underground mine galleries.…”
mentioning
confidence: 99%
“…In order to predict the wireless radio communication channel performances, the XLIM-SIC laboratory has developed a radio propagation simulator [28,[36][37][38], based on a 3D ray tracing associated to the Geometrical Optics laws (GO) and the Uniform Theory of Diffraction (UTD). Input data are the environment modelled in three dimensions by facets (finite planes), the maximum number of electromagnetic interactions (reflection on facets, diffraction on dihedron, i.e., two facets with a common edge, and refraction through facets), in addition with antennas features of transmitters and receivers, studied frequency, and so forth.…”
Section: Ray Tracing Simulatormentioning
confidence: 99%
“…Finally, the ray-based models are able to treat tunnel environments of any shape, even in dynamical scenario [20] with trains moving inside the tunnel between the antennas. In addition, it had been explored extensively by Maurer and coworkers to study vehicle-to-vehicle scenario [21,22] and shown to agree well with measurements [23][24][25][26][27][28]. However, the computational complexity of this method is directly related to the number of environment scatters and electromagnetic interactions.…”
Section: Introductionmentioning
confidence: 99%
“…To treat curved surfaces, the first intuitive approach consists in a tessellation of the curved geometry into multiple planar facets, as proposed in [10]. However, the surfaces' curvature is not taken into account in this kind of techniques and the impossibility to define rules for the choice of an optimal number of facets versus the tunnel geometry and the operational frequency was highlighted.…”
Section: Existing Studies On Radio Wave Propagation In Curved Tunnelsmentioning
confidence: 99%